On the Impact of Structural Reforms on Output and Employment : Evidence from a Cross-country Firm-level Analysis - Antoun de Almeida, Luiza (IMF Working Papers; Working Paper ;, 2018)
This paper analyzes the effects of selected structural reforms on output and employment in the short and medium term. It uses a comprehensive cross-country firm-level dataset covering both advanced and emerging market economies over the period 2003-2014. In line with previous studies, it finds that structural reforms have in general a positive impact on output and employment in the medium term. Furthermore, the paper also assesses whether the impact of structural reforms varies with firm-specific characteristics, such as size, leverage, profitability, and sector. We find evidence that firm characteristics do influence the effectiveness of structural reforms. These findings have relevant policy implications as they help policymakers tailor the design of structural reforms to maximize their payoffs, taking into account their heterogeneous impact on firms.